2017
DOI: 10.1177/1077546317707878
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling and response of a spur planetary gear system with journal bearings under gravity effects

Abstract: This paper focuses on the modeling method and the gravity-induced dynamic response of a spur planetary gear system with journal bearings. The lumped-parameter model of a planetary gear system with journal bearings is established. Both contact on drive-side and back-side of the tooth are considered simultaneously. Linear and nonlinear bearing force models are introduced into the system model separately to take the planet bearing oil-film forces into account. A demonstration is given to show the adopted nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Furthermore, gravity effects on the balance position of the floating inner gear ring (Figure 1(a)) were greater than that of the non-floating planetary gears (Figure 1(b)). Liu et al [14] studied the action of gravity on the motion trajectory of components in a planetary system and observed that gravity effects enlarge the orbits of the planetary gears (see in Figure 1(c)).…”
Section: Gravity Effects On Time-domain Dynamic Responsementioning
confidence: 99%
“…Furthermore, gravity effects on the balance position of the floating inner gear ring (Figure 1(a)) were greater than that of the non-floating planetary gears (Figure 1(b)). Liu et al [14] studied the action of gravity on the motion trajectory of components in a planetary system and observed that gravity effects enlarge the orbits of the planetary gears (see in Figure 1(c)).…”
Section: Gravity Effects On Time-domain Dynamic Responsementioning
confidence: 99%
“…Some studies have been conducted for the planetary gear stage using journal bearings in planet gears. In the simulation-based investigation in [13], it was found that the changing clearance in the journal bearings affects the gear backlash and teeth forces. The investigations in [14] concluded that the load-sharing characteristics of planetary gears are related to the parameters of the journal bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Guo and Parker 36 showed that the nonlinearity caused by bearing clearance can decrease the resonances in helicopter gear sets. Also, the dynamic behavior of spur planetary gear in different backlashes was investigated by Liu et al 37 through a lumped-parameter model, which considered the nonlinearity introduced by the gravity effect and bearing oil film. They used Newmark integration to calculate the dynamic responses.…”
Section: Introductionmentioning
confidence: 99%